Representasi Perempuan Dalam Foto Jurnalistik Petinju Perempuan di Armenia: Kajian Semiotika (JURNAL ILMIAH SOSIOLOGI: SOROT, 2022)
Photojournalism is a medium to describe a situation to make it more accessible to the public. sometimes a photo can also tell hidden meanings by reading the signs that appear in a photo. The photo of the female boxer belongs to photographer Nazik Armenakyan. In the photo, a woman is seen wearing clothes and skirts, as well as boxing gloves. Nazik Armenakyan's photo was posted on the website of The New York Times and has an interesting perspective on how an Armenian female boxer is framed in a photojournalism. The formulation of this research focuses on the meaning contained in the representation of women in photojournalism by Nazik Armenakyan. This qualitative research method with a critical perspective uses the semiotic theory of Roland Barthes in finding the meaning of a photo by analyzing the meaning of denotation, connotation, as well as myths and ideologies. The conclusion obtained based on the results of the analysis that has been carried out is the representation of women in photos of boxers in Armenia as a form of resistance against women who are not only able to do women's domestic work, but also can do jobs and activities that can be done by men. Keywords: journalism photography, semiotics, women.